Jesus of Nazareth : Jew from Galilee, Savior of the World - Schröter, Jens, 1961- (Book collections on Project MUSE., 2014)
Jesus of Nazareth continues to fascinate. From antiquity onwards countless people have found meaning for their lives through Jesus' teaching. His life led to the establishment of a community that subsequently grew into what is today the world's largest religion. At the center of the Christian faith stands the confession that this Jesus is both "true human being and true God."In Jesus of Nazareth, noted German New Testament scholar Jens Schröter directly addresses the connection between Jesus' humanity and divinity-how the historical Jesus can also be the Christ of confession. Schröter begins b.